2018
DOI: 10.47535/1991ojbe040
|View full text |Cite
|
Sign up to set email alerts
|

How Multinational Corporations Use Lobbying and Advocacy to Mitigate Political Risks

Abstract: In their international activities multinational corporations (MNCs) face various risks. Political risk is one of them. Expropriations, transfer and convertibility restrictions, breach of contracts, acts of terrorism, domestic political violence or other adverse regulatory changes and/or negative government action represent forms of political risks. Incorporating political risk in their risk management strategies becomes a necessity for MNCs in their search for profits and new markets. This article presents how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Bakre (2008) and Amusan (2018) stated that the presence of MNCs has benefited the elites, those in power, but has left communities around where these resources are extracted languishing in poverty and economic misery. This argument was further communicated by Iftinchi and Hurduzeu (2018) and Adeola et al (2021), who asserted that:…”
Section: The Global Power Of Mncsmentioning
confidence: 91%
See 1 more Smart Citation
“…Bakre (2008) and Amusan (2018) stated that the presence of MNCs has benefited the elites, those in power, but has left communities around where these resources are extracted languishing in poverty and economic misery. This argument was further communicated by Iftinchi and Hurduzeu (2018) and Adeola et al (2021), who asserted that:…”
Section: The Global Power Of Mncsmentioning
confidence: 91%
“…Leonard (1980) also explained that MNCs greatly influence many politicians in developing countries. Supporting this view, Iftinchi and Hurduzeu (2018) revealed that "MNCs use lobbying and advocacy to engage with governments and politicians in the country of origin and host countries to mitigate political risk".…”
Section: The Global Power Of Mncsmentioning
confidence: 99%